The extent to which Mu'tah University students in the course of advanced football are able to practice the training tasks from their perspective - Bilal Aldmour; Essam Abu Shehab (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aimed at identifying the differences between the results of pre and post tests in regard to the extent to which the students of advanced football have the ability to practice training football from their perspective due to the variables of academic courses, academic year, estimation, the student's classification, and the training courses in football. The study sample consisted of  (38) students from the students of the faculty of sport sciences who enrolled in the course of advanced football. The researchers developed a questionnaire, and the validity of arbitrators was used in developing them. The researchers used several statistical methods in order to find out the results using the statistical package (SPSS). The study results showed that there were statistically significant differences at the level (α≤0.05) in favor of the post test for the student's classification variable (Student student's category), while the results revealed that there were no statistically significant differences for the other variables (academic year, estimation, and the training courses in the domain of football). Based on the results, the researcher recommended the necessity of enhancing the content of the course of advanced football regarding the theoretical domains (psychological preparation, and tactical preparation).